(untitled) (Ozone Therapy Global Journal, 2013)
Symptoms such as pain, lameness, muscle weakness, decreased activity, etc are part of daily practice in veterina ry clinics. The standar d therapies including antiinflammatories, anal ges i cs or su rgery and ot hers, improve or resolve proble ms normally, but sometimes the side effects of these therapies prevent their use. On the other hand, their high costs discourage the owner from using them. Ozone treatments in human medicine has been well documented and scientifically corroborated years ago. Good examples of this are the large number of publications and the quality of the specialized conferences. In veterinary medicine we still have a long way to go. The purpose of this work was to study the anti-inflammatory and analgesic effects of the ozone an d of the growth factors platelet-derived with activated ozone in can ine species. The animals were divided into two groups; in group 1 were placed animals diagnosed with osteoarthritis, in group 2 were animals with spinal pain or pain in the extremities. In group 1, the animals were treated with ozone and growth factors and in group 2 with ozone only.In group 1, 85% showed a significant improvement and in group 2, about 93%.This study shows an open door to a whole new world for the application of ozone therapy in veterinary medicine.